A Rare Occurrence of Scalp Metastasis in Hepatocellular Carcinoma: Case Report - Chaudry, Samreen Javed; Ranjha, Fajar Rafi; Butt, Sumera; Nawaz, Samaha (Indian Journal of Medical and Paediatric Oncology, 2021)
Hepatocellular carcinoma (HCC) is the most prevalent primary liver malignancy and the fifth most common cancer worldwide. Extrahepatic spread in this type of cancer is most commonly seen in the lungs and lymph nodes and less commonly in the skeletal system. Skull metastases are exceedingly rare, with an incidence of 0.5 to 1.6% reported to date. We report a similar case of a middle-aged Asian male patient with parietal scalp swelling that was initially diagnosed as meningioma. Surgical resection was performed at a local facility. The abdominal computed tomography scan did not reveal any primary or metastatic lesion. After much deliberation, multiparametric magnetic resonance imaging was requested that showed multiple lesions in the liver. Metastatic scalp lesion should be considered a differential diagnosis in HCC regardless of liver symptoms.
Keywords: hepatocellular carcinoma; meningioma; scalp metastasis